The omission of pumice prophylaxis on bracket failure rates after using self-etch primers: a randomised controlled clinical trial - Thevadass Kaminii; Zakaria Nor Nadia; Othman Siti Adibah (Australasian Orthodontic Journal)
To investigate orthodontic bond failure rates and the associated effectiveness of pumice prophylaxis as a preparatory step before applying self-etching primers (SEP).